The role played by gender in viral hepatitis. (August 2014) - Bernabucci, Veronica; Villa, Erica
Abstract: Although not a classical target for estrogens, the liver is a target for their action and is sensitive to their deprivation. The occurrence of menopause is accompanied by a chain of events depending on the progressive estrogen deprivation that eventually leads to a shift from a low inflammatory to a high inflammatory state. This has a series of well-known consequences in many different organs and tissues (bone, heart, brain, body fat etc.) among which the liver is particularly interesting. The consequences are extremely evident in HCV-positive women in whom HCV infection and menopause cooperate to induce higher necro-inflammatory features, increased hepatic steatosis and eventually faster progression of fibrosis. In addition, menopause is the strongest negative factor for sustained viral response (SVR) in HCV-positive females, especially HCV genotype 1 (in whom menopause was the only independent factor for failure of antiviral therapy). This suggests that HCV-positive women should be treated early during fertile age to obtain maximal response to antiviral therapy.